1992
DOI: 10.1002/1097-0142(19920901)70:5<1044::aid-cncr2820700506>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Serum alpha-L-fucosidase. A useful marker in the diagnosis of hepatocellular carcinoma

Abstract: Background and Methods. The value of serum alpha‐L‐fucosidase activity in the diagnosis of hepatocellular carcinoma (HCC) was investigated by determining the enzyme activity levels in 21 patients with HCC, 76 patients with cirrhosis, 22 patients with other malignant neoplasms, and 23 healthy subjects. Results. The serum alpha‐L‐fucosidase activity level in patients with HCC (575.76 ± 212.86 nmol/ml/h) was significantly higher than that found in patients with cirrhosis (274.55 ± 138.97 nmol/ml/h; P < 0.001) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 14 publications
3
44
0
Order By: Relevance
“…However, there are some reports that have indicated that AFP has low sensitivity and specificity for its high false-positive and false-negative rates and is, therefore, only of limited utility in differentiating HCC from benign hepatic disorders (Zhou et al, 2006); these authors noted that patients with acute exacerbation of viral hepatitis but no HCC may also have markedly increased AFP levels. To improve sensitivity and specificity of any clinical detection, other biomarkers have been utilized (in addition to AFP) including measures of a-fucosidase lysosomal enzyme (Giardina et al, 1992) and of hepatocyte-produced pro-inflammatory cytokines (such as IL-2, -6, and -8) (Falasca et al, 2006). In the current study, AFP-as a differentiating marker between cirrhotic and HCC-bearing patients-had a 100% sensitivity and 86% specificity.…”
Section: Discussionsupporting
confidence: 63%
“…However, there are some reports that have indicated that AFP has low sensitivity and specificity for its high false-positive and false-negative rates and is, therefore, only of limited utility in differentiating HCC from benign hepatic disorders (Zhou et al, 2006); these authors noted that patients with acute exacerbation of viral hepatitis but no HCC may also have markedly increased AFP levels. To improve sensitivity and specificity of any clinical detection, other biomarkers have been utilized (in addition to AFP) including measures of a-fucosidase lysosomal enzyme (Giardina et al, 1992) and of hepatocyte-produced pro-inflammatory cytokines (such as IL-2, -6, and -8) (Falasca et al, 2006). In the current study, AFP-as a differentiating marker between cirrhotic and HCC-bearing patients-had a 100% sensitivity and 86% specificity.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, this explanation is not supported by recent studies that show a decrease of AFU expression in tumoral liver tissues compared to normal tissues [54]. AFU measurement is useful in association with AFP in the early diagnosis of HCC [55]. Moreover, there is a positive correlation between AFU levels and tumor size in HCC patients [56].…”
Section: Human Carbonyl Reductasementioning
confidence: 99%
“…All samples were studied following the completion of the collection period; however, AFU activity was assayed within 30 days after collection (17). This step was taken to avoid any possible alterations in AFU activity after this period (18).…”
Section: Ii-human Studymentioning
confidence: 99%